Widowhood, social networks, and mental health among Chinese older adults: The moderating effects of gender - Tang, Dan; Mair, Christine A.; Hu, Qing (Frontiers in Psychology, 2023)
Objectives: This study aimed to examine the three-way interaction between widowhood, social ties, and gender and its effects on older adults’ mental health, including depressive symptoms and life satisfaction, in the context of China. Methods: Participants were 7,601 Chinese older adults. Their social network was divided between family and friendship ties, and their mental health was measured by depressive symptoms and life satisfaction. Linear regression was employed to analyze the associations between widowhood, social networks, and mental health, as well as to explore the moderating effect of gender. Results: Widowhood is associated with more depressive symptoms, but not with life satisfaction, while family and friendship ties are associated with less depressive symptoms and greater life satisfaction. Furthermore, the lack of family ties is associated with more depressive symptoms for widowed men compared to married older men, while it is associated with lower life satisfaction for widowed women compared to married older women. Conclusion: Family ties are the most important social support resource for Chinese older adults, especially for the widowed group. The vulnerability of older widowed men who lack family ties in China deserves public concern and attention.